Peningkatan Akurasi Interpretasi Aliran Darah pada Citra Color Doppler Echocardiography (CDE) dengan Metode De-Aliasing - Shindy Yohanda; Sri Oktamuliani (Universitas Andalas, 2025)
Color Doppler Echocardiography (CDE) is an echocardiographic imaging technique that utilizes the Doppler effect principle to produce images of the heart. However, CDE images often contain aliasing artifacts that can hinder the interpretation of blood flow. This study aims to eliminate aliasing in CDE images of the apical 4-chamber view through the application of a de-aliasing method using MATLAB R2016b, and to evaluate the performance of this method in improving the accuracy of blood flow interpretation across all cardiac structures. The de-aliasing method corrects folded velocity values by extending the Nyquist velocity range. The results show that the maximum velocity value increased after the de-aliasing process, indicating that the Nyquist velocity range was successfully expanded. Furthermore, the method effectively reconstructed the folded velocity values back into a valid range. Visual errors in the form of color inversion were corrected by adjusting the color scheme of the image. Evaluation of the de-aliasing method’s performance demonstrated an improvement in the accuracy of blood flow interpretation throughout the cardiac structures.